STUDI KASUS IMPLEMENTASI MODEL KOMUNIKASI PEMASARAN SOSTAC PADA CAFE 99% COFFEE & EATERY - Safarwati Putri, Meri; Wilamadina, Ratu (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to determine the effect of education level and income level on interest in cash waqf with religiosity as a mediating variable. This study is quantitative in nature. The population consists of 90 Muslim civil servants. Data were collected using a questionnaire with a Likert scale, validity and reliability testing, and hypothesis testing using SmartPLS 4.0 software. The results of the study show that education level has a positive and significant effect on religiosity, income level has a positive and significant effect on religiosity, education level has no effect on interest in cash waqf, income level has a positive and significant effect on interest in cash waqf, and religiosity has a positive and significant effect on interest in cash waqf. Education level has a positive and significant effect on interest in monetary waqf with religiosity as a mediating variable, and income level has a positive and significant effect on interest in monetary waqf with religiosity as a mediating variable. Therefore, it is recommended that the government organize regular religious programs in the work environment of Muslim civil servants because religiosity has been proven to be a major factor in driving interest in monetary waqf.